Effects and action mechanisms of lotus leaf (Nelumbo nucifera) ethanol extract on gut microbes and obesity in high-fat diet-fed rats - Yanan, Zhang; Lu, Ma; Lu, Zhang; Jinhai, Huo; Weiming, Wang (Frontiers in Nutrition, 2023)
Objective The present study aimed to clarify the effect of the lotus leaf ethanol extract (LLEE) on the mechanism of antiobesity and the intestinal microbiota of obese rats. Methods A total of 40 specific pathogen-free (SPF) male Sprague–Dawley (SD) rats were split into the blank control group, the model control group, the Orlistat capsule control group, and the LLEE group. All the groups were intervened and fed specific diets for 5 months. During the experiment, we evaluated the rats' body weight, length, serum biochemical indicators, and inflammatory factor levels. After dissection, the liver; epididymal and perirenal white adipose tissue (WAT); and the contents of the cecum were collected for pathological evaluation and intestinal flora analysis. Results Lotus leaf alcohol extract can significantly reduce the serum total cholesterol, triglyceride, and low-density lipoprotein cholesterol levels. It also decreases the accumulation of fatty deposits in the liver of rats and the levels of serum inflammatory factors IL-6 and TNF-α and increases the level of IL-10. Lotus leaf alcohol extracts significantly increased the abundance of Muribaculaceae in the intestinal flora of rats, reduced the abundance of pro-inflammatory bacteria Firmicutes, and relieved fatty liver and other inflammation and diseases caused by a high-fat diet. Besides, the ethanol extract of the lotus leaf significantly regulated the abundance of Ruminococcus, suggesting that the ethanol extract of the lotus leaf may prevent hyperlipidemia. Conclusion We elucidated the effects and action mechanisms of LLEE on obesity in high-fat diet-fed rats to provide suggestions for regulating intestinal flora through dietary intervention and thus improving blood lipid metabolism.